Civil Society or Democracy? A Dutch Paradox - Aerts, Remieg (BMGN - Low Countries Historical Review, 2010)
Since the 1990s, research has been carried out worldwide into the relationship between ‘civil society’ (an organised, self-aware society) and the formation of democracy. Dutch historians have to date shown little interest in this field of research, although the case of the Netherlands is an interesting one, both historically and in terms of current affairs. This article makes a case for the relevance of Dutch history to the debate on civil society in relation to three points. Firstly, where civil society is a phenomenon of the eighteenth and above all the nineteenth centuries, the society of the Republic demonstrates that a corporatist order can show characteristics of a civil society. Secondly, the factor of religion can be an important element in the promotion of social commitment. Thirdly, Dutch history flags up a paradox: it seems that a highly developed, civil society can rather limit than promote the need for political democracy and the recognition of an independent political sphere. This article is part of the special issue ’The International Relevance of Dutch History’.